2015
DOI: 10.4028/www.scientific.net/amr.1109.424
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Methylene Blue over Cr Doped TiO<sub>2</sub> and Cr Doped TiO<sub>2</sub> Supported TUD-1 Photocatalysts

Abstract: A series of visible light driven photocatalysts of Cr-doped TiO2 and Cr-doped TiO2 supported on TUD-1 have been successfully synthesized via surfactant-free sol-gel method followed by wet impregnation procedure. XRD analysis revealed that both anatase and rutile phases existed in Cr-doped TiO2 samples. After loading onto TUD-1, both Ti and Cr were incorporated in the highly porous siliceous matrix. As observed, more tetrahedrally coordinated Ti species was formed in Cr-doped TiO2 after supporting onto TUD-1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Unlike silica aerogel, it can be easily produced via a comparatively simple and cost-efficient procedure. Recently, our research group reported the use of TUD-1 as a support for TiO2 nanoparticles [17,18]. The synthesized photocatalysts demonstrated favorable photocatalytic responses in the photodegradation of cationic and anionic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike silica aerogel, it can be easily produced via a comparatively simple and cost-efficient procedure. Recently, our research group reported the use of TUD-1 as a support for TiO2 nanoparticles [17,18]. The synthesized photocatalysts demonstrated favorable photocatalytic responses in the photodegradation of cationic and anionic dyes.…”
Section: Introductionmentioning
confidence: 99%